The influence of nucleus dates waste and ceramic wastes in sustainable concrete - Radwa Defalla Abdel Hafez; Raghda Osama Abd-Al Ftah; Khaled Abdelsamie (Sustainable Structures)
Recycling has progressed recently, turning specific non-renewable resources into renewable ones. This has led to a considerable increase in research on using waste materials such as ceramic and nucleus date waste as alternative aggregate materials in buildings. They suggest using aggregate from nucleus dates rubbish and ceramic waste to reduce the amount of waste in the environment and address material shortages at building sites. This study was aimed at determining whether the incorporation of ceramic waste aggregates (CWA) and nucleus dates aggregate (NDA) instead of coarse aggregate can improve strength ultra-high-performance concrete (SHPC) properties. Ten SEC combinations were prepared: 10%, 20%, and 30% of NDA, CWA, or a combination of both. After testing, quartz powder (Q.P) or silica fume (S.F.) can increase the UHPC by enhancing its mechanical characteristics. Waste as construction materials could have substantial technological, economic, and environmental advantages when employed within a sustainable development framework. The study's conclusions proved that replacing NDA or CWA can improve the qualities of SHPC, especially when replacing 10% of the original material.